KH. MUHAMMAD MUHADJIRIN AMSAR AL-DARI DAN KONTRIBUSINYA DALAM BIDANG HADITS - Untung Margono (DIRASAT: Jurnal Studi Islam dan Peradaban, 2019)
So many Indonesian Ulama, especially who experts in the field of hadith, their books are still taught in various halaqah and Islamic boarding school. One of the references in the hadith book that is used as a reference is the Book of Tanqīḥ al-Qawl al-Ḥathīth Syarḥ Lubāb al-Ḥadīth by Shaykh Nawawī al-Bantānī (d. 1879). This book is a copy of the book of Munabbihāt ‘alā al-Isti’dād li Yawm al-Ma’ād by Imam Ibn Ḥajar al-Athqalanī. Meanwhile, Shaykh Muhadjirin Amsar ad-Dari is a scholar who quite well known in the hadith works especially the explanation of the Book BulËgh al-MarÉm. This article is focused on the description of the expertise of Sheikh Muhajirin Amsar ad-Dari in the study of hadith.